Scale invariance of transtensional horsetail structures at the tip of strike-slip faults. Examples from Victoria Land, Antarctica - STORTI, Fabrizio; ROSSETTI, FEDERICO; SALVINI, Francesco (2004)
A deep knowledge of the dynamic and kinematic processes governing faulting is a basic requirement for seismic hazard assessments. Despite important progresses have been made on the mechanics and surface expression of faulting, on the evolution of the internal architecture of fault zones and fault systems, and on the interaction modes among adjacent faults, further research is needed for better constraining their 4-D seismogenic potential. In particular, the tip regions of regionally sized strike-slip fault systems are characterised by complex structural architectures that include faults with significant compressional and extensional components. These faults typically strike obliquely to the principal displacement zone of the parent fault system and their spatial distribution is related to the sense of motion of the latter. Stress concentration at fault tips makes these regions the potential candidates for large magnitude earthquakes. Exhumed fault zones and fault systems provide valuable opportunities for studying fossil seimogenic zones. A Cenozoic network of intraplate right-lateral strike-slip fault systems occurs in North Victoria Land, Antarctica. In particular, the western sector of the southern tip region of the Priestley Fault is well exposed near the Italian Base at Terra Nova Bay. Occurrences of pseudotachylyte-bearing fault cores both along the principal displacement zone and along splay faults arranged in a crustal-scale horsetail transtensional structure, indicate the exposed fault network was active at seismogenic depth in Late Cenozoic times. In this contribution, we describe the structural architecture at the termination of the Priestley Fault. We show that transtensional fault splaying from the principal displacement zone is preserved as the most efficient displacement accommodation mechanism for strike-slip faults whose length ranges from metric to more than a hundred of kilometres. The mechanical reasons for this evidence and the seismic hazard implications are discussed.